EFFECTIVENESS OF THE SELF-HELP GROUP (SHG) METHOD ON BLOOD PRESSURE IN PRODUCTIVE WOMEN WITH HYPERTENSION - Luluk Fauziyah Januarti; Soliha Soliha; Sofi Yulianto (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Productive women are an age group that is vulnerable to experiencing health problems. This problem increases as a person gets older. The increase in age experienced by productive women causes all systems and functions to decline. This shows that hypertension sufferers' awareness of taking medication is still low. So this can be minimized with community empowerment activities, one of which is a self-help group (SHG). The aim of this research is to determine the effect of self help group (SHG) on the blood pressure of productive women with hypertension. The design used was